Effects of Essential Newborn Care Training on Fresh Stillbirths and Early Neonatal Deaths by Maternal Education - Chomba, Elwyn (2016)
Background: Infants of women with lower education levels are at higher risk for perinatal mortality. Objectives: We explored the impact of training birth attendants and pregnant women in the Essential Newborn Care (ENC) Program on fresh stillbirths (FSBs) and early (7-day) neonatal deaths (END) by maternal education level in developing countries. Methods: A train-the-trainer model was used with local instructors in rural communities in six countries (Argentina, Democratic Republic of the Congo, Guatemala, India, Pakistan, and Zambia). Data were collected using a pre-/post-active baseline controlled study design. Results: A total of 57,643 infants/mothers were enrolled. The follow-up rate at 7 days of age was 99.2%. The risk for FSB and END was higher for mothers with 0-7 years of education than for those with ≥8 years of education during both the pre- and post-ENC periods in unadjusted models and in models adjusted for confounding. The effect of ENC differed as a function of maternal education for FSB (interaction p = 0.041) without evidence that the effect of ENC differed as a function of maternal education for END. The model-based estimate of FSB risk was reduced among mothers with 0-7 years of education (19.7/1,000 live births pre-ENC, CI: 16.3, 23.0 vs. 12.2/1,000 live births post-ENC, CI: 16.3, 23.0, p < 0.001), but was not significantly different for mothers with ≥8 years of education, respectively. Conclusion: A low level of maternal education was associated with higher risk for FSB and END. ENC training was more effective in reducing FSB among mothers with low education levels.